Contusions of the Abdomen - Avendaño, L. (1919)
We are therefore in the presence of a case of violent death, an accidental death, whose true cause is that we have to investigate, to illustrate to the authority about the way acted trauma, indicating what the injury has caused the death of Heredia. To do this we have to check the forensic examination of the body, beginning, as is provision for external inspection.